2013
DOI: 10.1111/jbfa.12036
|View full text |Cite
|
Sign up to set email alerts
|

The Information Content of Dividend Surprises: Evidence from Germany

Abstract: This paper reconsiders the issue of share price reactions to dividend announcements. We use the difference between the actual dividend and the analyst consensus forecast as obtained from I/B/E/S as a proxy for the surprise in the dividend announcement. Using data from Germany, we find significant share price reactions after dividend announcements. We use panel methods to analyze the determinants of the share price reactions and find evidence in favour of the cash flow signaling hypothesis and dividend clientel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…De Cesari (2012) also agreed that ownership concentration is positively associated with dividend payout, which prevents the conflict between controlling and minority shareholders. Contrary to this, Andres, Betzer, Bongard, Haesner, and Theissen (2013) indicated that ownership concentration affects dividend payout, depending on the type of controlling shareholders among German firms. Based on the above discussions, the hypothesis is thus developed as follows:…”
Section: Ownership Concentration and Dividend Payoutmentioning
confidence: 71%
“…De Cesari (2012) also agreed that ownership concentration is positively associated with dividend payout, which prevents the conflict between controlling and minority shareholders. Contrary to this, Andres, Betzer, Bongard, Haesner, and Theissen (2013) indicated that ownership concentration affects dividend payout, depending on the type of controlling shareholders among German firms. Based on the above discussions, the hypothesis is thus developed as follows:…”
Section: Ownership Concentration and Dividend Payoutmentioning
confidence: 71%
“…With respect to the different ownership structures that corporations have, the finance literature shows increasing interest in the family business model due to its peculiarities. In terms of agency relationships, concentrated ownership and the predominance of family control imply greater concern over conflicts of interests between dominant shareholders and minority outside investors (Burkart et al., ; and Andres et al., ), as opposed to the classical owner–manager agency problem. In this respect, a number of empirical studies investigate the differences between family and non‐family firms in terms of firm performance (see, e.g., Anderson and Reeb, ; Maury, ; Villalonga and Amit, ; and Andres, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Although extensive empirical studies (e.g., Aharony & Swary, ; Al‐Yahyaee et al, ; Easton, ; Kane et al, ; Kumar, ; Lonie et al, ; Michaely, Thaler, & Womack, ; Pettit, ; Sumanna, ) have addressed whether changes in dividend levels convey important information to market participants (the signalling theory), the evidence is mixed. On one hand, consistent with the signalling theory, several studies found that the stock market reacts positively (negatively) to announcements of dividend increases (decreases) (e.g., Aharony & Swary, ; Andres, Betzer, Bongard, Haesner, & Theissen, ; Dasilas & Leventis, ; McClusky, Burton, Power, & Sinclair, ; Pettit, ), unexpected dividend increases (decrease) (e.g., Woolridge, ), stock split announcements (e.g., Liljeblom, ), and dividend initiations (omissions) (e.g., Michaely et al, ).…”
Section: Literature Review and Theorymentioning
confidence: 68%